A novel keratin 12 mutation in a German kindred with Meesmann's corneal dystrophy. Issue 5 (1st May 2000) - Corden, L D; Swensson, O; Swensson, B; Rochels, R; Wannke, B; Thiel, H J; McLean, W H I
Abstract : AIM: To study a kindred with Meesmann's corneal dystrophy (MCD) to determine if a mutation within the cornea specific K3 or K12 genes is responsible for the disease phenotype. METHODS: Slit lamp examination of the cornea in four members of the kindred was carried out to confirm the diagnosis of MCD. The region encoding the helix initiation motif (HIM) of the K12 polypeptide was polymerase chain reaction (PCR) amplified from genomic DNA derived from affected individuals in the kindred. PCR products generated were subjected to direct automated sequencing. Restriction enzyme analysis employing Ban I was used to confirm the presence of the mutation in affected individuals of the family. RESULTS: Sequencing of the K12 gene in an affected individual from the family revealed a novel heterozygous missense mutation (413A→C), predicting the substitution of a proline for a glutamine at codon 130 (Q130P) in the HIM of the K12 protein. The mutation was excluded from 50 normal, unaffected individuals by restriction enyzme analysis and was therefore unlikely to be a common polymorphism. CONCLUSION: A novel missense mutation in the K12 gene leads to MCD in a German kindred. Missense mutations have now been identified within the region encoding the helix initiation motif of the K12 protein in eight of 11 MCD kindreds analysed at the molecular level.